THE POLITICS OF DESIRE: MALE AGGRESSION AND FEMALE AGENCY IN POST-LIBERALIZATION HINDI CINEMA - Rajkumar, Johnson (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper critically examines the representation of sexual harassment and coercion in 1990s Hindi cinema, a decade often celebrated for its romantic and family-oriented narratives. While Bollywood’s romantic films of this decade foregrounds love and youthful desire, they simultaneously embedded subtle forms of sexual violence, such as stalking, eve-teasing and coercive advances within courtship rituals. Drawing on feminist film theory and Laura Mulvey’s concept of the “male gaze,” the study argues that these cinematic portrayals blurred the line between romance and harassment, presenting male aggression as endearing and female resistance as coyness destined to yield to persistence. Through textual analysis of popular films, this paper highlights how Bollywood constructed a hierarchy of sexual violence, extreme acts like rape were demonised when committed by villains, while “moderate” acts of harassment by heroes were normalised, trivialised and celebrated. The paper argues that these representational strategies not only reinforced patriarchal ideologies but also shaped cultural perceptions of romance, agency and gender roles. The paper underscores how 1990s Hindi cinema functioned as an ideological apparatus that legitimized coercion as love and perpetuated gendered hierarchies.